Effectiveness and economic evaluation of rhTPO and rhIL-11 in the treatment of cancer therapy induced thrombocytopenia based on real-world research - Gong, Fa-Min; Liu, Fu-Yue; Ma, Xue; Ma, Song-Tao; Xiao, Hong-Tao; Jiang, Gang; Qi, Ting-Ting (Frontiers in Pharmacology, 2024)
Objective：Based on real-world research, we aimed to evaluate the effectiveness and economy of recombinant human thrombopoietin (rhTPO) and recombinant human interleukin 11 (rhIL-11) in the treatment of cancer therapy induced thrombocytopenia (CTIT). Methods：We retrospectively collected clinical data of patients with CTIT who were treated with rhTPO or rhIL-11 in a single cancer hospital from January 2020 to December 2021. Propensity score matching (PSM) was applied to avoid possible selection bias. The measurements of effectiveness analysis were the platelet compliance rate, days of medication, days of compliance, highest platelet count after medication, platelet count elevation before and after medication, and the lowest platelet count after next-cycle cancer therapy. The economic evaluation was performed according to the results of the effectiveness evaluation. At the same time, patients were stratified according to type of tumor and grade of thrombocytopenia for subgroup analysis. Results：A total of 262 patients were collected and 174 patients were enrolled after PSM, 87 in the rhTPO group and 87 in the rhIL-11 group. In all patients, there were no significant differences in the platelet compliance rate, mean days of medication, median days of compliance, median highest platelet count after medication, and the median platelet count elevation before and after medication between the two groups (p > 0.05), but the median lowest platelet count after next-cycle cancer therapy in the rhTPO group was lower than that in the rhIL-11 group (p = 0.014). The subgroup analysis showed that the rhTPO group had longer mean days of medication than the rhIL-11 group in patients with hematological malignancies (p = 0.042), and a lower median lowest platelet count after next-cycle cancer therapy in patients with grade I/II thrombocytopenia than rhIL-11 group (p = 0.022), with no significant difference in other outcome indicators (p > 0.05). As there was no statistically significant difference in platelet compliance rate between the two groups, the cost-minimization analysis showed that the rhIL-11 group had lower treatment costs than the rhTPO group. Conclusion：RhTPO and rhIL-11 showed similar effectiveness in the treatment of CTIT, but rhIL-11 was more advantageous in economic cost.